2014
DOI: 10.1371/journal.pone.0111166
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Changes in the Expression of the Clock Protein PERIOD1 in the Rat Limbic Forebrain and Hypothalamus: Role of Stress Type, Time of Day, and Predictability

Abstract: Stressful events can disrupt circadian rhythms in mammals but mechanisms underlying this disruption remain largely unknown. One hypothesis is that stress alters circadian protein expression in the forebrain, leading to functional dysregulation of the brain circadian network and consequent disruption of circadian physiological and behavioral rhythms. Here we characterized the effects of several different stressors on the expression of the core clock protein, PER1 and the activity marker, FOS in select forebrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 75 publications
1
31
2
Order By: Relevance
“…Further, studies have been published investigating the effect of stress on the expression of clock genes in rodents. However, different stressors were applied, such as post-traumatic stress disorder (Koresh et al, 2012), severe stressors (chronic unpredictable stress; Jiang et al, 2013), and systemic glucocorticoid administration and restraint stress (Al-Safadi et al, 2014). Furthermore, the use of different strains of animals (Erburu et al, 2015; Schaufler et al, 2016) and time points of day for decapitation makes it difficult to compare our results with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies have been published investigating the effect of stress on the expression of clock genes in rodents. However, different stressors were applied, such as post-traumatic stress disorder (Koresh et al, 2012), severe stressors (chronic unpredictable stress; Jiang et al, 2013), and systemic glucocorticoid administration and restraint stress (Al-Safadi et al, 2014). Furthermore, the use of different strains of animals (Erburu et al, 2015; Schaufler et al, 2016) and time points of day for decapitation makes it difficult to compare our results with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…One shared symptom observed in patients with schizophrenia and depression is the presence of aberrant circadian rhythms4950, including insomnia350. Several studies employing different stressors observed impaired circadian rhythms of molecular clock proteins including Per1, Clock, and Cry2 in the amygdala, the limbic forebrain and the hypothalamus5152. These studies suggest that stress can disrupt circadian rhythms of brain areas related to emotional processing.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the environmental light-dark cycle is a powerful zeitgeber that adjusts rhythms of period circadian clock gene expression in the SCN. In contrast, daily rhythms in period circadian clock gene expression outside of the SCN tend to be sensitive to diverse behavioral and physiologic factors, including changes in feeding schedules, body temperature, glucocorticoid release, and stress (5)(6)(7)(8). By identifying zeitgebers that act in a region-specific manner, it is possible to gain insight into the functional importance of extra-SCN rhythms.…”
Section: Michael Verwey Sherin Al-safadi and Shimon Amirmentioning
confidence: 99%
“…This daily rhythm of adrenal glucocorticoid release-corticosterone in rodents-is also important for the synchronization or entrainment of daily oscillations of PER2 expression in the limbic forebrain (6). PER1 expression in the same brain areas also responds to acute stressors, and these effects depend on whether a processive stressor (forced swim, restraint) or a systemic stressor (interleukin-1β or 2-deoxy-D-glucose injection) is used (7). Most of these manipulations failed to adjust PER1 and PER2 expression rhythms in the SCN (6,7).…”
Section: Michael Verwey Sherin Al-safadi and Shimon Amirmentioning
confidence: 99%
See 1 more Smart Citation